Analisis Kesiapan Kerja Mahasiswa: Peran Pengalaman Lapangan Industri (PLI) dan Soft Skill Melalui Mediasi Motivasi Kerja - Tessa Aida Trisna; Indra Saputra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the influence of soft skills and Industrial Field Experience (IPC) on students' readiness to enter the workforce by utilizing work motivation as a mediating variable. A quantitative approach was used in this study by applying the Structural Equation Modeling Partial Least Square (SEM-PLS) analysis technique. Data were collected through an online survey involving 102 students of the Cosmetology and Beauty Study Program at Padang State University. The results showed that both soft skills and industrial field experience had a significant influence on job readiness, both directly and through the mediation of work motivation. Work motivation was proven to be able to strengthen the relationship between the independent variables and student job readiness. This finding indicates that work motivation plays an important role as a psychological mechanism that connects non-technical skills and practical experience with readiness to enter the professional world. This research model showed strong predictive power, reflected in the R-square value of job readiness of 0.751. This value indicates that 75.1% of the variability in job readiness can be explained by the model involving soft skills, IPC, and work motivation. The implications of these results are very important for higher education institutions. To prepare graduates who are better prepared to face the challenges of the workplace, strengthening soft skills and providing relevant industrial field experience should be a primary focus of the curriculum. Furthermore, strategies to increase student work motivation must be systematically designed to optimize the results of this competency development.